(untitled) (Nigerian Dental Journal, 2025)
A detailed understanding of root canal morphology is essential for successful root canal, mandibular second premolar usually consists of a single root with a single root canal but two roots with multiple canals has been reported. This study aims to bring to attention such variations in root and canal numbers and a successful, nonsurgical endodontic management of mandibular left second premolar with two separate roots and four distinct root canals. Tooth was tender on percussion with electric pulp tests revealed tooth 35 to be totally non-responsive. Digital periapical radiograph showed two rooted tooth 35 with coronal radiolucency in close communication with the pulp and diagnosis of acute apical periodontitis of tooth 35 was made. Root canal treatment done locating all four canals; mesio lingual, mesio-buccal, disto-lingual and disto-buccal